INTERACTION BETWEEN ADIPOSE TISSUE AND PHYSICAL ACTIVITY IN THE REGULATION OF BODY WEIGHT: A CONCEPTUAL NARRATIVE REVIEW (FUDMA JOURNAL OF SCIENCES, 2024)
The modern obesity pandemic is characterized by difficulty in achieving and maintaining weight loss. This suggests the existence of a physiological control mechanism to maintain body mass. However, this same mechanism did not prevent obesity pandemic. The aim of this review is to explain this conundrum. Online searches of Google Scholar, PubMed, and Scopus were conducted. The main variable under physiological control is not a fixed body/fat mass but balance between energy intake and expenditure. The expenditure includes resting metabolic rate, physical activity related energy expenditure and thermic effect of food. Increased energy expenditure triggers increased energy intake to match expenditure levels and counters any weight loss. This matching of energy input and output can happen at any body/fat mass. In other words, body/fat mass can settle at any level with energy intake matched to expenditure; the so-called settling point mechanism. The particular body/fat mass settling point is determined by the availability of energy and degree of expenditure enabled by the environment. The modern environment with abundance of nutrients and motorized work has been termed obesogenic environment. It facilitates higher body mass and hence increased resting metabolic rate energy expenditure to support the increased body mass; this triggers more energy intake and thus more mass gain in a positive feedback vicious cycle. In conclusion, shifting emphasis away from body mass control to energy balance allows one to explain both the modern obesity pandemic as well as why it is so difficult to achieve and maintain weight loss.
Keywords: Adipose tissue; Energy expenditure; Physical inactivity; Obesity; Narrative review